Factors Affecting Indonesian Higher Education Institution Students’ Academic Achievement in the Industry 4.0 Era - Aditya Andika; Fabiola J. Y. Louwisia; Claudia F. Susilo; Aurellia Victoria (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Industry 4.0 presents new challenges for Higher Education Institutions in Indonesia. Jobs in this era requires intellectual capabilities at a higher level. One of the ways to measure intellectual capabilities is through Academic Achievement in the form of Grade Point Average (GPA). Organizations around the world, including in Indonesia, want employees with high GPA. Therefore, it is imperative for Higher Education Institutions in Indonesia to understand the factors affecting Students’ Academic Achievement. This study conducts literature reviews to find and analyse factors affecting Indonesian Students’ Academic Achievement in Industry 4.0 era. This study finds 28 factors. Based on these factors, this study develops development initiatives that Indonesian Higher Educations Institutions in Indonesia can do in order to improve Indonesian students’ academic achievement.